Comparison of The Use of Glycerol and Sorbitol as Plasticizers on The Quality of Bioplastics Based on Cellulose-Chitosan - Qolbi, Nur Nisa Aeni; Zidni Azizati; Ika Nur Fitriani (Department of Chemistry Faculty of Science and Technology Walisongo, 2024)
The accumulation of plastic waste poses significant environmental and health problems. One effort to mitigate this issue is the development of bioplastics. Correspondingly, the primary materials used in this research were cellulose from teak (Tectona grandis) wood powder, chitosan, glycerol, and sorbitol. This study aimed to compare the effectiveness of glycerol and sorbitol as plasticizers. Glycerol is considered cost-effective, renewable, biodegradable, and environmentally friendly, while sorbitol, which is also non-toxic and naturally abundant, can enhance product durability by inhibiting water evaporation. Both materials exhibit good potential as plasticizers; therefore, their comparison is necessary. The research stages included extracting cellulose from teak wood powder, synthesizing cellulose-chitosan-glycerol and cellulose-chitosan-sorbitol bioplastics, and characterizing the resulting materials. The results exhibited the presence of functional groups such as –OH, C-H, and C-O, which were typical of cellulose, as well as N-H groups, characteristic of chitosan. The best quality for glycerol-based bioplastics was achieved with the addition of 0.5 mL of glycerol, yielding a tensile strength of 5.79 MPa, elongation of 10.3%, water absorption of 43.43%, and a degradation time of 17 days. For sorbitol-based bioplastics, the best quality was obtained with the addition of 1 mL of sorbitol, resulting in a tensile strength of 6.23 MPa, elongation of 13.7%, water absorption of 67.46%, and a degradation time of 14 days. Based on these results, sorbitol is more recommended than glycerol as a plasticizer in this study.